2022
DOI: 10.1039/d2fo02994d
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene alleviates multiple-mycotoxin-induced toxicity by inhibiting mitochondrial damage and ferroptosis in the mouse jejunum

Abstract: The contamination of foods and feeds with multiple mycotoxins threatens human and animal health after they accumulate in the food chain, producing various toxic effects. Feeds are almost universally contaminated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Ferroptosis is a form of non-apoptotic regulatory cell death caused by the Fenton reaction, which is driven by LPO and iron accumulation . Several studies have demonstrated that ferroptosis is directly associated with mitochondrial oxidative stress and that ferroptosis can inhibit GPX4 expression while raising LPO generation. , Co-exposure to zearalenone, DON, and aflatoxin B1 has been proven in recent research to produce jejunal injury in mice, in addition to the mechanism involved in ferroptosis . In this investigation, we discovered that DON exposure can alter ferroptosis-related indices and parameters, as evidenced by an increase in iron concentration, TfR protein expression, and the lipid peroxide products MDA and 4HNE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroptosis is a form of non-apoptotic regulatory cell death caused by the Fenton reaction, which is driven by LPO and iron accumulation . Several studies have demonstrated that ferroptosis is directly associated with mitochondrial oxidative stress and that ferroptosis can inhibit GPX4 expression while raising LPO generation. , Co-exposure to zearalenone, DON, and aflatoxin B1 has been proven in recent research to produce jejunal injury in mice, in addition to the mechanism involved in ferroptosis . In this investigation, we discovered that DON exposure can alter ferroptosis-related indices and parameters, as evidenced by an increase in iron concentration, TfR protein expression, and the lipid peroxide products MDA and 4HNE.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Co-exposure to zearalenone, DON, and aflatoxin B1 has been proven in recent research to produce jejunal injury in mice, in addition the mechanism involved in ferroptosis. 40 In this investigation, we discovered that DON exposure can alter ferroptosis-related indices and parameters, as evidenced by an increase in iron concentration, TfR protein expression, and the lipid peroxide products MDA and 4HNE. Moreover, genes associated with ferroptosis (PTGS2, ACSL4, and HAMP1) were elevated, whereas FTH1, SLC7A11, GPX4, FPN1, and FSP1 were downregulated.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the mice were given at least 1 week to adjust to the experimental environment. Forty mice were divided into four groups, each containing ten mice: control (corn oil daily by oral gavage with sterile water, Ctrl group); corn oil daily by oral gavage with 1.5% DSS in sterile water (DSS group); lycopene (12 mg/kg BW) daily by oral gavage with sterile water (LY group), the dose was determined according to previous studies; , and lycopene (12 mg/kg BW) daily by oral gavage with 1.5% DSS in sterile water (LYD group). Mice in the LY and LYD groups were given lycopene orally by gavage for 12 weeks, and after 3 weeks of lycopene gavage, the LYD mice were exposed to 1.5% DSS.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that administering oral lycopene supplements at a dosage of 10 mg/kg body weight per day significantly reduced oxidative stress, mitochondrial dysfunction, and ferroptotic cell death caused by a combination of mycotoxins in the jejunum tissue of mice. These mycotoxins included ZEN at 10 mg/kg body weight, DOX at 1 mg/kg body weight, and AFB1 at 0.5 mg/kg body weight [87]. The study found that lycopene's ability to activate the body's antioxidant system played a crucial role in protecting against the toxic effects triggered by AFB1.…”
Section: Inhibition Of Oxidative Stressmentioning
confidence: 95%